2016
DOI: 10.1155/2016/7172948
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patellar Tendon Reflex Responses Using Second-Order System Characteristics

Abstract: Deep tendon reflex tests, such as the patellar tendon reflex (PTR), are widely accepted as simple examinations for detecting neurological disorders. Despite common acceptance, the grading scales remain subjective, creating an opportunity for quantitative measures to improve the reliability and efficacy of these tests. Previous studies have demonstrated the usefulness of quantified measurement variables; however, little work has been done to correlate experimental data with theoretical models using entire PTR r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…An accelerometer was used to demonstrate the difference between myelopathy patients and healthy volunteers in terms of the PTR response 7 , and another study reported an accuracy of 89.62%, according to the NINDS score, using machine learning classifiers 30 . A motion capture system was also used to demonstrate the knee angle increase dependent on the tapping force in healthy participants 15 , 16 and its usability for cerebral palsy patients 31 . As for MMG, there was no evidence of PTR quantification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accelerometer was used to demonstrate the difference between myelopathy patients and healthy volunteers in terms of the PTR response 7 , and another study reported an accuracy of 89.62%, according to the NINDS score, using machine learning classifiers 30 . A motion capture system was also used to demonstrate the knee angle increase dependent on the tapping force in healthy participants 15 , 16 and its usability for cerebral palsy patients 31 . As for MMG, there was no evidence of PTR quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Surface electromyography (EMG) has been the most commonly applied method 11 , 12 which, while convenient, can be subject to difficulties with respect to electrode placement 13 . Other methods included attaching force transducers 14 , accelerometers 7 , and motion analysis 15 , 16 . However, these experimental set-ups are difficult to use clinically, and there is little evidence that focuses on the muscle movement itself during the tendon reflex.…”
Section: Introductionmentioning
confidence: 99%
“…9 , 10 NINDS (National Institute of Neurological Disorders and Stroke) and Mayo clinic reflex grading scales are two widely accepted ordinal scales utilized for the PTR assessment. 11 But, these scales lack temporal data and have high inter-rater variability. 12 , 13 Therefore, improved tools and techniques are required to quantify PTR responses accurately to enhance the utility of DTR examination.…”
Section: Introductionmentioning
confidence: 99%
“…Some work has attempted to quantify the test by performing motion analysis [15] in cerebral palsy children [16] and also proposed a new iPhone application to measure the reflex response [17]. Other studies have attempted to model the patellar reflex as a response from a theoretical second-order system [18].…”
Section: Introductionmentioning
confidence: 99%